2012
DOI: 10.1002/jbmr.1591
|View full text |Cite|
|
Sign up to set email alerts
|

High serum adiponectin predicts incident fractures in elderly men: Osteoporotic fractures in men (MrOS) Sweden

Abstract: Adipocytes and osteoblasts share a common progenitor, and there is, therefore, potential for both autocrine and endocrine effects of adiponectin on skeletal metabolism. The aim of the present study was to determine whether high serum adiponectin was associated with an increased risk of fracture in elderly men. We studied the relationship between serum adiponectin and the risk of fracture in 999 elderly men drawn from the general population and recruited to the Osteoporotic Fractures in Men (MrOS) study in Goth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
1
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 36 publications
2
44
1
5
Order By: Relevance
“…Nevertheless, most association studies showed negative correlations between BMD and adiponectin in premenopausal and postmenopausal women and in men (30,34,35). In the Osteoporotic Fractures in Men study, the risk of fracture increased in parallel with increasing serum adiponectin (36). Although adiponectin levels were low in obese and diabetic patients (37), in our study it increased with increasing fat mass in men and mediated for the negative effect of fat on BMD as well.…”
Section: Discussionmentioning
confidence: 57%
“…Nevertheless, most association studies showed negative correlations between BMD and adiponectin in premenopausal and postmenopausal women and in men (30,34,35). In the Osteoporotic Fractures in Men study, the risk of fracture increased in parallel with increasing serum adiponectin (36). Although adiponectin levels were low in obese and diabetic patients (37), in our study it increased with increasing fat mass in men and mediated for the negative effect of fat on BMD as well.…”
Section: Discussionmentioning
confidence: 57%
“…Several studies have suggested that higher levels of serum adiponectin are associated with incident fractures in elderly men [22], [23]. Barbour and colleagues [24] found a significant association between serum adiponectin and all fractures in men but not in women.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, depletion of adiponectin has been shown to protect mice from ovariectomy-induced osteoporosis (30). Finally, a high adiponectin level has been shown to be associated with incident fractures in elderly males (31). In the present study, high plasma adiponectin levels were identified in patients with LDD.…”
Section: Discussionmentioning
confidence: 99%